2006
DOI: 10.1088/0953-8984/18/7/005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of giant magnetoresistance effect in the Ruddlesden–Popper phase Sr3Fe2−xCoxO7−δ: predominant role of oxygen nonstoichiometry and magnetic phase separation

Abstract: The magnetic and magnetotransport properties of the Sr 3 Fe 2-x Co x O 7-δ system (0.2 ≤ x ≤ 1.0) were systematically investigated. This oxide system exhibits a giant magnetoresistance (GMR) effect at low temperatures, reaching up to 80% in 7 T at 5 K.Ac-susceptibility measurements show that there exists a strong competition between ferromagnetic (F) and spin glass states, and the balance between these two magnetic states can be controlled by varying cobalt (x) and/or oxygen contents (δ). Importantly, the MR e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The isomer shift, δ, and quadrupole splitting of the paramagnetic components, ∆, determined using the least square fit are given inTable 3, from which we found that the isomer shift for doublet 2 is in good agreement with that of low-spin Fe 4+ and doublet 3 for Fe 3+ in an octahedral coordination[23]. In compari-son, the δ value of doublet 1 is intermediate to that of Fe 4+ and Fe 3+ (>0.30 mm/s) and hence is attributed to Fe 3+y due to the rapid ion exchange as commonly observed in ferrite structures at ordinary temperatures[24]. Thus, possibility of a charge disproportionation of the form 2Fe 4+ →…”
supporting
confidence: 82%
“…The isomer shift, δ, and quadrupole splitting of the paramagnetic components, ∆, determined using the least square fit are given inTable 3, from which we found that the isomer shift for doublet 2 is in good agreement with that of low-spin Fe 4+ and doublet 3 for Fe 3+ in an octahedral coordination[23]. In compari-son, the δ value of doublet 1 is intermediate to that of Fe 4+ and Fe 3+ (>0.30 mm/s) and hence is attributed to Fe 3+y due to the rapid ion exchange as commonly observed in ferrite structures at ordinary temperatures[24]. Thus, possibility of a charge disproportionation of the form 2Fe 4+ →…”
supporting
confidence: 82%
“…The 3d transition metal oxides with perovskite-related intergrowth crystal structure include different systems with remarkable electrical and magnetic properties. For example, high- Tc superconductivity has been reported in the layered compound La 2−x Ba x CuO 4 , while large negative magnetoresistance in (La,Sr) 3 Mn 2 O 7 and other layered compounds , has been observed. Recently, the mixed conductor properties of the Ruddlesden−Popper (R-P) series of phases (La,Sr) n +1 (Fe,B) n O 3 n +1 with B = Fe, Co, Ni, Ti, Sc and n = 2 and 3 have been explored to utilize these materials in electrochemical applications at high temperatures, such as solid oxide fuel cells and oxygen permeation membranes .…”
Section: Introductionmentioning
confidence: 99%
“…Like its n = ∞ (cubic perovskite-type) sister compound SrFe 1−x Co x O 3−δ , the present system exhibits ferromagnetism with increasing Co substitution x. The magnetic moment of Sr 3 Fe 2−x Co x O 7−δ is about 2.5−2.7 µ B per Fe/Co site for x of 0.3−1.0, depending upon synthesis conditions and/or the amount of δ [2,3]. Moreover, it shows negative magnetoresistance [4,5], reminding us of the colossal magnetoresistive Mn oxides La 2−2x Sr 1+2x Mn 2 O 7 .…”
Section: Introductionmentioning
confidence: 79%